Based on AHP–VW–PSR for groundwater vulnerability assessment and pollution prevention in industrial–agricultural regions: a case study of the Zhongyuan oilfield - Yawei Zhang; Junpei Chen; Defang Zhang; Xincen Dong; Huimeng Su; Zhipeng Li; Wenfang Chen (Geocarto International)
Groundwater is essential for agriculture. This study assesses groundwater vulnerability in the Zhongyuan oilfield using the ‘pressure–state–response’ (PSR) model, integrating the analytic hierarchy process (AHP) and variable weight (VW) method to enhance spatial heterogeneity. Spearman correlation and univariate sensitivity analysis identify key factors, including oil extraction activities, net recharge, and depth to water, public expenditure, and aquifer thickness. Results show 25.48% of the area has high vulnerability, 57.67% moderate, and 16.85% low. Receiver operating characteristic (ROC) analysis validates the model performance, showing that the AHP–VW–PSR model achieves a higher area under the curve (AUC) value of 0.83, compared to 0.71 for the AHP–PSR model, indicating significantly improved predictive accuracy. Based on groundwater vulnerability, groundwater resource supply function, and ecological protection zone, the area is divided into development and utilization zone, normal zone, and protection zone. This framework optimizes groundwater management, providing scientific guidance for similar regions.